Analisis Pengungkapan Kecurangan pada Sektor Pemerintah melalui Peran Big Data - Fella Ardina Cahyani; Slamet Trimah; Mulyadi Mulyadi; Fili Mukaromah; Herina Manurung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted to determine the role of big data in disclosing fraud in the government sector. This study uses the literature review method with a qualitative descriptive approach by collecting secondary data by reading journals about the role of big data in disclosing fraud. After analyzing the journal, it was found that big data has a positive influence on fraud detection and also plays a role in audit investigations. In addition, big data through social media also has a role in helping to calculate the suitability of the amount of wealth of government officials through the goods they display on social media or flexing.